Sequential ion irradiations on Fe-Cr and ODS Fe-Cr alloys. (December 2020) - Šćepanović, M.; Leguey, T.; García-Cortés, I.; Sánchez, F.J.; Hugenschmidt, C.; Auger, M.A.; de Castro, V.
Highlights: Sequential dual He/Fe irradiation at RT of a model Fe14Cr alloy and an ODS steel. Both show small (<2nm) irradiation induced bubbles, mostly in the ferritic matrix. TEM investigations of the ODS steel suggest that nanoparticles remain quite stable. DB PAS suggest that He associates with vacancies introduced by the Fe+ irradiation. Abstract: Oxide dispersion strengthened steels are candidate materials for nuclear reactor applications due to a powerful combination of properties, such as reduced activation, high-temperature strength and increased creep resistance. The dispersion of nanometric oxide particles in the steel matrix may also enhance radiation resistance by acting as trapping sites for irradiation induced defects. In this work, an Fe–14Cr–2 W–0.3-Ti–0.3Y2 O3 (wt%) steel and a model Fe-14Cr (wt%) alloy were sequentially irradiated with He + and Fe + ions up to 15 dpa and 8000 appm to simulate fusion radiation damage. Their microstructural stability was investigated by positron annihilation spectroscopy and transmission electron microscopy. Transmission electron microscopy studies show that under these irradiation conditions there are no significant changes in the mean size, qualitative chemical composition and number density of nanoparticles, although the irradiation appears to induce a slight coarsening of the smaller nanoparticles. Both materials exhibit very small (<2 nm) irradiation-induced bubbles, with similar sizes but lower number density in the ODS steel. Positron annihilation spectroscopy results show the presence of irradiation induced open volume defects, much more noticeable in the model alloy. In both alloys, helium appears to associate with the newly formed vacancy-type defects introduced by the subsequent Fe + irradiation.